Technology and Provenance Analysis of Glass Fragments from an Ottoman Bathhouse (Hamam) in Kyparissia, Peloponnese, Greece. Issue 2 (15th December 2017) - Palamara, E.; Zacharias, N.; Germanidou, S.; Gerolymou, K.; Palles, D.; Kamitsos, E.I.
ABSTRACT: This study focuses on the analysis of a post-medieval assemblage of glass vessels and tableware, recovered from an Ottoman bathhouse in Kyparissia, SW Peloponnese, Greece. The chemical composition of the samples was estimated using SEM/EDS, whereas minor and trace elements were identified by qualitative XRF analysis. Raman spectroscopy was applied in order to examine the connectivity of the silicate glass matrix in more detail. The acquired data indicate significant chemical variations among the samples, especially in regards to the alkali source and the decolourant used. Moreover, one high-lead glass has also been identified. The provenance analysis, which was based on the statistical treatment of the resulted and published analytical data, indicated that the different glass types originated both from the eastern regions of the Ottoman Empire and from glassmaking centres in central and northern Europe. The determination of technology and provenance of the assemblage provided with valuable new information regarding the production and trading network of glass in mainland Greece during the Ottoman rule.